(Acetylacetone 3-hydroxy-2-naphthoylhydrazonato-kappa 3 O,N',O')(methoxo-kappa O)oxidovanadate(V) - Wong, H.W.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The tridentate Schiff base ligand in the title compound, [V(C(16)H(14)N(2)O(3))(CH(3)O)O], has its O, N and O' atoms spanning three basal positions of the square-based-pyrimidally VV atom. The fourth basal site is occupied by a methoxo ligand, which results from a deprotonated methanol solvent molecule, and the oxido ligand occupies the apical position. The hydroxy H atom forms an intramolecular O-H...N hydrogen bond with an N-atom acceptor site.